Digital gratification: short video consumption and mental health in rural China - Zhang, Chen; Zhu, Bochen (Frontiers in Public Health, 2025)
BackgroundIn recent years, short videos have become increasingly popular in rural China, yet their impact on mental health remains underexplored. While prior studies have debated the psychological effects of social media, little is known about how short-form video consumption affects rural populations.ObjectiveThis study investigates the causal relationship between short video consumption and mental health among rural residents in China.MethodsWe use longitudinal data from the China Family Panel Studies and apply a Difference-in-Differences strategy to estimate the impact of frequent short video usage on mental health. To address self-selection and staggered treatment timing, we employ Propensity Score Matching and heterogeneity-robust difference-in-differences estimators. Robustness checks include placebo tests and an event study analysis.ResultsWe find that short video consumption appears to improve mental health among rural residents. The effect is immediate and significant only in the first year of exposure, but fades in subsequent periods. Mechanism analysis suggests that the improvements are driven by enhanced entertainment and information access rather than increased social interaction. The effects are more pronounced in economically underdeveloped and less pandemic-affected regions, but not evident among urban residents.ConclusionShort videos provide short-term mental health benefits for rural Chinese residents by enriching their leisure and information access, especially in less developed areas. However, their positive effect is transient and cannot offset pandemic-related stress. Policy efforts should aim to balance the benefits of digital entertainment with potential risks such as addiction and information overload.